Percutaneous nephrolithotripsy for renal pelvis stone in a crossed fused ectopic kidney: a case report - Sarpal, Rajeev; Chaudhary, Tarun; Biswas, Manoj; Agarwal, Shikhar; Mittal, Ankur (International Journal of Research in Medical Sciences, 2016)
Crossed renal ectopia is the second most common fusion anomaly of the kidney after horseshoe kidney. The incidence of both fused and unfused cases is 1 in 7000 in autopsies. Percutaneous nephrolithotripsy (PCNL) is a well-established technique in the surgical management of nephrolithiasis. The conventional fluoroscopic guidance of PCNL will be of limited value in ectopic anomalous kidneys due to the abnormal anatomical landmarks with consequent compromise of the procedure’s safety. A 30-year old male patient, previously healthy, presented to our urology outpatient clinic complaining of dull flank pain of six month duration with tenderness in the right renal area and an enlarged right kidney and 1 episode of gross haematuria. Radiological investigations showed left side crossed ectopia with nephrolithiasis. Patient was managed successfully by fluoroscopic guided percutaneous nephrolithotripsy. The position of the stone-containing ectopic kidney can make it easy to reach the pelvis of the target kidney without injuring any adjoining structure. The superimposition of the different soft tissue densities in the radiologic view may limit the ability of the operator to distinguish between different tissue identities. Laparoscopic guidance can represent as a practical solution to this technical problem.